The Influence of Work Life Balance, Mental Health and Burnout on the Work Motivation of Employees at The Bogorejo Community Health Center, Blora District - Sari, Dhiastika Nanda; A. Rohendi, A. Rohendi; Syarifuddin, Didin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the influence of work-life balance, mental health, and burnout on employee work motivation at the Bogorejo Community Health Center in Blora Regency. The background of this study is based on the phenomenon of low work motivation reflected in high rates of lateness and absenteeism, as well as pre-survey results that indicate an imbalance between work and personal life, mental health problems, and high levels of burnout. This study used a quantitative method with a survey approach, involving 56 respondents who were employees of the Bogorejo Community Health Center. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that work-life balance and mental health had a significant positive effect on work motivation, while burnout had a significant negative effect on work motivation. These findings provide important implications for human resource management in the health sector, particularly in designing policies to improve the welfare and work motivation of health workers.